THE GROWTH AND DEVELOPMENT OF Spodoptera pectinicornis (Lepidoptera: Noctuidae) PROVIDED WITH ENHANCED NUTRITION FROM Pistia stratiotes FEEDING VIA FERTILIZATION - Aphrodyanti, Lyswiana; Soedijo, Samharinto; Millati, Tanwirul; Aidawati, Noor (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
A monophage herbivorous insect called S. pectinicornis can be utilized to biologically control the weed Pistia stratiotes. Insect mass reproduction followed by release into the target weed area is one technique that can be used. The quality of the feed must be taken into consideration during maintenance in order to increase the fitness of S. pectinicornis insects and enable them to function at their best. The fertilization procedure can improve the nutritional value of P. stratiotes as a feed source. The experiment involved applying NPK fertilizer to P. stratiotes at 6 different levels: 0 g (control); 5 g; 10 g; 15 g; 20 g; and 25 g. The findings demonstrated that when NPK fertilizer was applied to Pistia stratiotes, S. pectiniconis larvae, pupae, and imago had a better chance of surviving than controls. S. pectinicornis showed improved insect growth and development since its lifespan was shorter than controls at every developmental stage. The ideal NPK fertilizer dose for maintaining Pistia stratiotes as feed during S. pectinicornis propagation is 15g/20 L of water.